Korean American Immigrant Women’s Mammography Use in Korea: Factors Associated with Medical Tourism - Mi Hwa Lee; Joseph Merighi; Leslie Cofie; Bryan Rogers (Social Sciences)
This study examined social determinants associated with Korean American immigrant women’s mammography use in Korea after immigration to the United States. Data from a cross-sectional survey were obtained from 187 women in Los Angeles County, California. More than one-quarter (28.3%) of the respondents reported returning to Korea for a mammogram after immigrating to the United States. Multivariable logistic regression revealed that compared to those who had their first mammogram in Korea, Korean American immigrant women who had their first mammogram in the United States were less likely to return to Korea for subsequent screenings (AOR = 0.02, 95% CI: <0.001, 0.05); also, those who had employer-based health insurance in the United States were less likely to get a mammogram in Korea after immigration (AOR = 0.01, 95% CI: <0.01, 0.18). Findings suggest that women familiar with the Korean healthcare system and who are uninsured or have inconsistent healthcare coverage in the United States may seek care in Korea. To promote adherence to breast cancer screening guidelines among Korean American immigrant women residing in the United States, greater access to free or low-cost screening services and breast cancer screening education is warranted to reduce the risk of later stage breast cancer detection resulting from medical tourism.